Penyuluhan Dan Konsultasi Hukum Tentang Pencegahan Dan Penanganan Kasus Kekerasan Seksual Di SMA Muhammadiyah Kota Kupang - A. Resopijani; Simplexius Asa; Reny R Masu; Windasari N Sudiarta; Rizal S. Thene; Daud Yaferson Dollu; Kornelia Melasari; Petrus Merio Mamoh (KADARKUM: Jurnal Pengabdian Kepada Masyarakat, 2026)
Sexual violence is a serious human rights violation that significantly affects children and adolescents who are still in their developmental stages. Schools, as spaces for education and character building, can unfortunately become locations where sexual violence occurs—whether verbal, physical, or digital. Therefore, legal education is essential to prevent and respond to such cases. In this context, the Faculty of Law of Universitas Nusa Cendana conducted a legal outreach program at SMA Muhammadiyah Kupang to enhance students’, teachers’, and staff’s understanding of sexual violence prevention and handling. The material was delivered in a panel format by experts in Procedural Law through lectures, discussions, Q &A sessions, and case studies. Participants were also given the opportunity to consult on past or ongoing issues, with a restorative justice approach offered as an alternative mechanism focused on victim recovery. The activity strengthened participants’ knowledge of Law No. 12 of 2022 on Sexual Violence Crimes and Law No. 35 of 2014 on Child Protection. Students and teachers showed strong enthusiasm, demonstrated by their active engagement throughout the session. They reported gaining clearer guidance on identifying, preventing, and addressing sexual violence in schools. This program proved highly beneficial and is expected to be continued in other schools to broaden legal awareness and strengthen community protection. Keywords: Sexual Violence; Socialization; Adolescents; Prevention;